Interior lighting as an afterthought in residential planning - Vargas, Maria Patricia A. (College of Home Economics, University of the Philippines Diliman, 2013)
ABSTRACT Based on literature, many American and European homeowners regard lighting as an afterthought in the planning of their houses. To find out whether the same is true of Filipino homeowners, this study gathered data from middle-class Filipinos, whose houses were built in selected villages in Antipolo City from 1990 to 2010. The reasons and implications for either their neglect or observance of lighting strategies were determined. These implications were based on the elements of appropriate lighting strategies by lighting designers Loe & Tregenza (1998) that is information, control, and energy. Only indoor lighting in selected common areas of houses were assessed in the study. The study was descriptive in nature and utilized the multi-method approach to research. An interview guide and observation guide were used to extract information from 10 interview respondents. Measurements were presented in the form of lighting layouts. Additional data from 20 survey respondents was collected using a survey questionnaire. 19 of 30 respondents discussed lighting strategies with an architect at the onset of the home planning. This number is not enough to generalize whether middle-class Filipino homeowners consider lighting strategies as an afterthought. A few respondents did not implement lighting strategies discussed due to budget constraints. Despite discussions on lighting strategies in the design development, respondents still encountered difficulties: the insufficiency of light, high cost in terms of electrical bills, and problematic maintenance. The depth of lighting discussions with building professionals was not extracted in this study. It could be that the discussions were limited to one element that compromised the other two elements of Loe & Tregenza's (1998) appropriate lighting strategies. Thus, the importance of discussing lighting strategies during design development was not established in the study.